2002
DOI: 10.1053/jhep.2002.32667
|View full text |Cite
|
Sign up to set email alerts
|

Transport of the sulfated, amidated bile acid, sulfolithocholyltaurine, into rat hepatocytes is mediated by Oatp1 and Oatp2

Abstract: The uptake of the sulfated bile acid sulfolithocholyltaurine (SLCT) was investigated in isolated rat hepatocytes and in HeLa cells transfected with complementary DNAs (cDNAs) of organic anion transporting polypeptides (Oatps) 1 and 2 cloned from rat liver. In hepatocytes, transport of SLCT was greatly reduced by bromosulfophthalein (BSP), estrone sulfate, the precursor bile acids cholyltaurine and lithocholyltaurine, and 4,4 -diisothiocyanostilbene-2-2 -disulfonic acid (DIDS). However, SLCT transport was insen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Similar reports demonstrate in vitro inhibition of OATP2B1 transport by grapefruit and orange juices as well as other herbal extracts (Satoh et al, 2005;Fuchikami et al, 2006). Rodent Oatp1a1 and -1a4 share similar substrates with OATP1A2, including unconjugated and conjugated bile acids, bromosulfophthalein, sulfated steroids, thyroid hormones, ouabain, ␤-lactam antibiotics, and fexofenadine (Cvetkovic et al, 1999;Reichel et al, 1999;Hagenbuch et al, 2000;Meng et al, 2002;van Montfoort et al, 2002;Nakakariya et al, 2008). Rat Oatp1a1 and Oatp1a4 can transport opioid peptides [D-Pen 2 ,D-Pen 5 ]-enkephalin and deltorphin II (Oatp1a1 only), which may be important in their transport across the blood-brain and blood-cerebrospinal fluid barriers Gao et al, 2000).…”
Section: Oatp1a2mentioning
confidence: 61%
“…Similar reports demonstrate in vitro inhibition of OATP2B1 transport by grapefruit and orange juices as well as other herbal extracts (Satoh et al, 2005;Fuchikami et al, 2006). Rodent Oatp1a1 and -1a4 share similar substrates with OATP1A2, including unconjugated and conjugated bile acids, bromosulfophthalein, sulfated steroids, thyroid hormones, ouabain, ␤-lactam antibiotics, and fexofenadine (Cvetkovic et al, 1999;Reichel et al, 1999;Hagenbuch et al, 2000;Meng et al, 2002;van Montfoort et al, 2002;Nakakariya et al, 2008). Rat Oatp1a1 and Oatp1a4 can transport opioid peptides [D-Pen 2 ,D-Pen 5 ]-enkephalin and deltorphin II (Oatp1a1 only), which may be important in their transport across the blood-brain and blood-cerebrospinal fluid barriers Gao et al, 2000).…”
Section: Oatp1a2mentioning
confidence: 61%
“…Uptake of CDF was digoxin-independent, suggesting that CDF may not be an Oatp2 substrate. However, recently, Meng et al (2002) demonstrated that digoxin did not inhibit the uptake of an Oatp2 substrate, sulfolithocholyltaurine. CDF appears to be an Oatp1 substrate based on bromosulfophthalein inhibition of CDF uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there was no description of the in vivo bile acid phenotype associated with those polymorphisms. In addition, whereas inherited disorders characterized by a relatively isolated elevated plasma bile acid level (hypercholanemia; part of the prefamily expressed on the hepatocyte sinusoidal membrane, such as Oatp1a1 ( Slco1a1 ), effi ciently transport unconjugated or sulfated bile acids, suggesting that these carriers participate in the hepatic uptake of those bile acid species in vivo ( 50,56,57 ). The high level of NTCP expression at the sinusoidal membrane of hepatocytes and NTCP's high affi nity for conjugated bile acids promotes their effi cient extraction from portal blood.…”
Section: Hepatocellular Transport Of Bile Acidsmentioning
confidence: 99%